2020
DOI: 10.3126/nh.v14i1.30612
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Botanical Extracts, Chemical Fungicides and Trichoderma harzianum Against Alternaria brassicicola Causing Leafspot of Cabbage

Abstract: Alternaria leaf spot caused by Alternaria brassicicola is one of the destructive diseases of crucifers and causes considerable loss in the yield and quality of the produce. An experiment was conducted in in vitro to evaluate the efficacy of six botanical extracts at three concentrations i.e. 5%, 10% and 15%, six chemical fungicides at five different concentrations i.e. 50ppm, 100ppm, 250ppm, 500ppm and 1000ppm and Trichoderma harzianum against Alternaria brassicicola. The study was carried out using poisoned f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Leaf spots, stunting, and damping-off are among the symptoms that may appear on young plants in seedbeds. Leaf spots caused by A. brassicicola start as tiny, black spots that quickly develop into circular lesions up to 1 cm in diameter (Pun et al, 2020). Alternaria brassicicola is a simple parasite that lives outside of its host saprophytically.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf spots, stunting, and damping-off are among the symptoms that may appear on young plants in seedbeds. Leaf spots caused by A. brassicicola start as tiny, black spots that quickly develop into circular lesions up to 1 cm in diameter (Pun et al, 2020). Alternaria brassicicola is a simple parasite that lives outside of its host saprophytically.…”
Section: Introductionmentioning
confidence: 99%
“…reported superior activity of clove against Alternaria alternata that causes postharvest infections in the dragon fruit (Hylocereus undatus). According toGadhi et al (2020), clovePun et al (2020) reported a growth inhibition of about 63% in A. alternata the causal agent of leaf spot of cabbage (Brassica oleraceae var. capitata) by a 10% concentration of fresh turmeric extracted in water.…”
mentioning
confidence: 99%